Pentingnya Proteksi Data Diri dari Cybercrime di Platform Digital bagi Generasi Alpha (Lembaga Pengembangan Kinerja Dosen, 2026)
Rapid advances in digital technology bring various benefits and risks, including the threat of cybercrime, which can particularly affect Generation Alpha. The purpose of this seminar was to raise awareness and understanding among students at SMK Bina Patriot of the importance of protecting personal data on digital platforms. The seminar was attended by 62 participants who are active internet users in their daily lives. The seminar was conducted interactively through lectures, case studies, and training on steps to protect personal data, such as creating secure passwords and managing privacy on social media. The evaluation of the results showed a significant increase in participants' understanding, reaching an average of 97%. It is hoped that this will become a strong foundation of digital literacy for the younger generation in facing the challenges of the cyber world wisely and safely. This increased understanding is expected to be a strong foundation for Bina Patriot Vocational School students to develop their digital literacy, which in turn will help them to be able to face the challenges of the digital world wisely, safely, and responsibly.